Analisis Kualitas Layanan dan Dampaknya Terhadap Kepuasan Nasabah di PT. Bank Central Asia (BCA) - Sania Eka Yanti; Tombang Daulat Ni Roha Harianja; Agung Wirakususma; Mohamad Zein Saleh (Manajemen Kreatif Jurnal, 2024)
In the current era, customers are more critical and intelligent in determining which bank to use so banks need to understand customer needs and preferences more deeply. Optimal service quality is one of the keys to retaining and attracting customers. The purpose of this study is to analyze service quality and its impact on BCA customer satisfaction, which is then expected to provide more insight into this matter. The research method used is qualitative with literature study data collection. The results of this study indicate that BCA’s service quality is very good, but still needs to be improved, especially regarding digital services. Then, service quality can have an impact on customer satisfaction.